2015
DOI: 10.1007/s10534-015-9875-3
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexes as a source of redox active MRI contrast agents

Abstract: This version is available at https://strathprints.strath.ac.uk/54085/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Ligands containing other pendent arms were later synthesized and the relaxivity of these complexes was studied. [40] As expected from the low total spin of these complexes, their relaxivity is modest, between 0.11 and 0.42 mM À 1 s À 1 . Moreover, the redox potential of these complexes was quite high (> 0.65 V) and they thus couldn't be used to target hypoxic cells or tissue.…”
Section: Copper Complexesmentioning
confidence: 77%
See 1 more Smart Citation
“…Ligands containing other pendent arms were later synthesized and the relaxivity of these complexes was studied. [40] As expected from the low total spin of these complexes, their relaxivity is modest, between 0.11 and 0.42 mM À 1 s À 1 . Moreover, the redox potential of these complexes was quite high (> 0.65 V) and they thus couldn't be used to target hypoxic cells or tissue.…”
Section: Copper Complexesmentioning
confidence: 77%
“…Moreover, the tertiary amines thereby created were more stable toward ligand oxidation which occurred during reduction‐oxidation studies. Ligands containing other pendent arms were later synthesized and the relaxivity of these complexes was studied [40] . As expected from the low total spin of these complexes, their relaxivity is modest, between 0.11 and 0.42 mM −1 s −1 .…”
Section: Redox‐associated Spin‐state Changementioning
confidence: 99%
“…75 However, with the advent of better imaging software and higher field strengths, limited relaxivity changes are less prohibitive. Spickett and collaborators 104 ( Figure 23) studied three series of Cu II macrocyclic frameworks (66)(67)(68), obtaining the reduced forms by using ascorbic acid as reductant. They observed considerably low r1 changes (0.11-0.44 mM -1 .s -1 ), the highest was reported for the member of the 67 family with X = -(CH2)2OH.…”
Section: T1 Probes Based On Metal Redox Statesmentioning
confidence: 99%
“…These complexes display relaxivities higher than those measured for LFB 28 and comparable with those reported for other Cu(II) complexes containing N or O-donor ligands that have complicated structures or are more difficult to obtain. [61][62][63] For instance, Reglinski and Spickett et al reported relaxivities in the range of 0.11-0.42 mM -1 s -1 for N-substituted macrocyclic Cu(II) complexes (9.4 T, 0.1 M NaCl in D2O). As noted in the introduction, Luxol fast blue (LFB), a well-known histological stain, has been tested as an MRI contrast agent, and has a comparatively poorer value of 0.09 mM -1 s -1 (aqueous solution at 4.7 T).…”
Section: Relaxivity Measurementsmentioning
confidence: 99%